Feasibility Study and Digital Market Competition Analysis at Pak Sabit Wonogiri Chicken Noodle UMKM Business - Muhammad Irfan; Agus Suyatno (LP2M IAIN Palopo, 2025)
Micro, small, and medium enterprises (MSMEs) in the culinary sector, such as chicken noodle stalls, are increasingly developing with the use of digital technology. This study analyzes the business feasibility and digital market competition at Mie Ayam Pak Sabit in Wonogiri. The method used is descriptive qualitative with data collection through interviews, observations, and financial report analysis. The results of the study indicate that this business is feasible to run based on market, digital marketing, and financial aspects. Marketing strategies through social media and effective financial management provide great opportunities for business expansion. Optimization of digital marketing channels and product diversification are recommended to increase competitiveness in a competitive market.